2018
DOI: 10.1530/rep-17-0566
|View full text |Cite
|
Sign up to set email alerts
|

The impact of infertility diagnosis on embryo-endometrial dialogue

Abstract: Initial stages of implantation involve bi-directional molecular crosstalk between the blastocyst and endometrium. This study investigated an association between infertility etiologies, specifically advanced maternal age (AMA) and endometriosis, on the embryo-endometrial molecular dialogue prior to implantation. Co-culture experiments were performed with endometrial epithelial cells (EEC) and cryopreserved day 5 blastocysts ( = 41 ≥ Grade 3BB) donated from patients presenting with AMA or endometriosis, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Although proof that these miRNAs derive from EVs is still lacking, it may be presumed that these embryo-derived miRNAs could be secreted via EVs. Interestingly in this regard, EVs isolated from human co-culture supernatant of endometrial epithelial cells and cryopreserved D5 blastocysts revealed significant alterations in miRNA expression in relation to the age of the blastocyst donors [46]. Eighteen EV-bound miR-NAs displayed altered levels in presence of blastocysts from advanced maternal-age subjects.…”
Section: Evs and Mirnasmentioning
confidence: 97%
See 1 more Smart Citation
“…Although proof that these miRNAs derive from EVs is still lacking, it may be presumed that these embryo-derived miRNAs could be secreted via EVs. Interestingly in this regard, EVs isolated from human co-culture supernatant of endometrial epithelial cells and cryopreserved D5 blastocysts revealed significant alterations in miRNA expression in relation to the age of the blastocyst donors [46]. Eighteen EV-bound miR-NAs displayed altered levels in presence of blastocysts from advanced maternal-age subjects.…”
Section: Evs and Mirnasmentioning
confidence: 97%
“…The target genes of these miRNAs are thought to mediate cellular activities such as adhesion and migration, suggesting that embryos could potentially modify the endometrial function [43]. Interestingly in this regard, EVs isolated from human co-culture supernatant of endometrial epithelial cells and cryopreserved D5 blastocysts revealed significant alterations in miRNA expression in relation to the age of the blastocyst donors [46]. Although proof that these miRNAs derive from EVs is still lacking, it may be presumed that these embryo-derived miRNAs could be secreted via EVs.…”
Section: Evs and Mirnasmentioning
confidence: 99%
“…However, some problems have emerged companied with the development of IVF. The outcome of IVF can be influenced by physical and physiological factors, on one hand, physical factors such as uterine contraction makes the embryo escape from the uterus (5); on the other hand, physiological factors such as age of the female patient, the age of infertility, the quality of the transplanted embryo, secretion of related hormones can also seriously affect the pregnancy rate (6,7). In addition, studies have confirmed that during the IVF transplant operation, the pathogens of the cervix may be brought into the uterine cavity, which will also affect the IVF outcome (8).…”
Section: Introductionmentioning
confidence: 99%
“…TFMPs participate in thrombus formation and clot propagation (Nomura and Shimizu, 2015). Moreover, following Alleviate PCOS by targeting PDCD4 to promote proliferation and inhibit apoptosis of cumulus cells New therapeutic strategy Zhao et al, 2019 Biomarkers for predicting PCOS Carvalho et al, 2017b Endometriosis Reflect the state of the inflammation and/or procoagulant system Munros et al, 2017 Increase total weight and impair macrophages' phagocytic ability Sun et al, 2019 Contribute to endometriosis by affecting inflammation, angiogenesis, and proliferation in the microenvironment of endometriotic lesions Khalaj et al, 2019 Prediction of successful embryo implantation Parks et al, 2018 Decrease of endometriosis fibrosis by reducing Collagen αI and CTGF mRNA expression Wu et al, 2018 Promote the occurrence of endometriosis and regulate angiogenesis Harp et al, 2016, Qiu et al, 2019 A non-invasive detection marker in the diagnosis of endometriosis Muth et al, 2015 EVs: Extracellular vesicles. PCOS: Polycystic ovary syndrome.…”
Section: Extracellular Vesicles and Polycystic Ovary Syndromementioning
confidence: 99%